Detection of bacteria in blood by centrifugation and filtration. - Bernhardt, M (1991)
Culture of blood is the most frequent means of diagnosing bacteremia. However, conventional blood culturing methods are slow in isolating bacteria. We developed a method for isolation of bacteria by centrifugation and filtration. Fresh human whole blood was inoculated with facultatively anaerobic and aerobic microorganisms (3 to 172 microorganisms per 5 ml). Seeded blood was then mixed with Ficoll-Hypaque (density, 1.149 +/- 0.002 g/ml) and centrifuged (386 x g) for 30 min at ambient temperature. The entire gradient (plasma, leukocytes, and Ficoll-Hypaque) was removed and filtered through a 0.22-micron membrane filter (Millipore). The filters were then placed on chocolate agar plates and incubated at 35 degrees C in a humidified atmosphere containing 5% CO2. For each bacterium tested, approximately 35 to 100% of the viable microorganisms were recovered when compared with control cultures (pour plates of seeded blood). All bacteria produced isolated colonies on filters after overnight incubation (18 h). This procedure may prove to be a more rapid method for isolating bacteria from clinical blood samples than the blood culture bottle technique.